2023
DOI: 10.2147/prbm.s422194
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Nexus of Emotional Intelligence and University Performance: An Investigation Through Perceived Organizational Support and Innovative Work Behavior

Zahid Shafait,
Jiayu Huang

Abstract: Purpose This study is based on the ability-based theory of emotional intelligence (EI), organizational support theory, and componential theory of creativity. This study intended to investigate organizational performance (OP) against academics’ EI in higher education institutions (HEIs) in China. This study further scrutinized perceived organizational support (POS) and innovative work behavior (IWB) as mediators among these associations. Similarly, the inter-link between POS and IWB was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…This body of work has illuminated the influence of emotional intelligence—a non-cognitive measure of intelligence—on organizational performance within higher education institutions in China. 46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This body of work has illuminated the influence of emotional intelligence—a non-cognitive measure of intelligence—on organizational performance within higher education institutions in China. 46 …”
Section: Discussionmentioning
confidence: 99%
“…This body of work has illuminated the influence of emotional intelligence-a non-cognitive measure of intelligence-on organizational performance within higher education institutions in China. 46 Our study introduces an intriguing dimension to the discourse: subjective age, despite the fact that some criticism arises on the influences of subjective age in older workers' outcomes. 47 Hayes' Model 14 allowed us to disentangle its moderating influence.…”
mentioning
confidence: 95%
“…Further, power distance has been used as mediator in previous studies (Robertson et al, 2016;Seppala et al, 2008). Robertson et al (2016) with a larger portion of population, hence responses collected from targeted sample can indiscriminately be generalized over population (Shafait & Huang, 2023a, 2023b. This study requested 1200 students from twenty-seven HEIs i.e., nine HEIs on average from three provinces.…”
Section: Dark Triad Power Distance and Academic Entitlementmentioning
confidence: 99%
“…Sullivan et al showed, using quantitative testing of physiological indicators, that exposure to green space can help students recover from stress and mental fatigue [5]. Additionally, studies indicate that fostering emotional intelligence has positive effects on university performance [6], enhances teacher creativity [7], and positively influences the learning outcomes of both students and teachers, as well as organizational performance [8,9]. This demonstrates the crucial importance of emotional well-being among knowledge workers for the development of a university.…”
Section: Of 28mentioning
confidence: 99%